Human Milk Glucocorticoid Levels Are Associated With Infant Adiposity and Head Circumference Over the First Year of Life - Pundir, Shikha; Gridneva, Zoya; Pillai, Avinesh; Thorstensen, Eric B.; Wall, Clare R.; Geddes, Donna T.; Cameron-Smith, David (Frontiers in Nutrition, 2020)
Human milk (HM) is a complex and dynamic biological fluid, which contains appreciable concentrations of the glucocorticoids, cortisol and cortisone. Experimental studies in non-human primates suggest the HM glucocorticoids’ impact on infant growth and body composition. In this current study, analysis is made of the relationships between HM glucocorticoid concentrations and the infant growth and development over the first year of life. HM was collected by lactating healthy women (n=18), using a standardised protocol, at 2, 5, 9 and 12 months after childbirth. Cortisol and cortisone concentrations in the HM were measured using liquid chromatography mass spectrometry. Infant weight, length and head circumference were measured by standard protocols and percentage fat mass (% FM) determined by whole body bioimpedance. Cortisol and cortisone concentrations were unaltered over the analysed lactation period (2 to 12 months), and were altered by infant sex. Although, HM cortisol was positively associated with infant percentage fat mass (% FM) (p=0.008) and cortisone positively associated with infant head circumference (p=0.01). For the first 12 months of life, the concentration of HM glucocorticoids levels was positively associated with infant adiposity (%FM) and head circumference. This preliminary evidence provides insight to a possible relationship between ingested HM glucocorticoids and infant body composition. Further studies are required to determine the mechanisms regulating HM glucocorticoids.